British Foreign Policy Under New Labour, 1997–2005 - Williams, P. author. aut Link
XIII, 263 p.
Keywords: This important new study provides a critical analysis of the foreign policies conducted during the first two terms of Tony Blair's government. It focuses upon the government's key foreign policy commitments; three of its most important international relationships (with the US, the European Union, and Africa); and how Blair's government dealt with five fundamental policy issues (political economy, defence, international development, intervention, and Iraq). It argues that throughout this period Labour's foreign policies attempted to paper over some important contradictions.